Distribution and sexual condition of Pottiaceae (Bryophyta) in Mexico - Peña Retes, Ana Paola; Delgadillo Moya, Claudio (Instituto de Ecología, A.C., 2020)
Background and Aims: The bryophytes are non-vascular plants that reproduce by spores, gemmae or fragments of gametophytes (diaspores); their distribution and survival depend on them. This contribution evaluates the role of the sexual condition on the distribution of Mexican Pottiaceae, a diverse and frequent moss family in Mexico. It is proposed that: a) the monoicous species exhibit a wide distribution in the country due to frequent sporophyte production, b) dioicous species that do not produce sporophytes show discontinuous or restricted distribution patterns and c) species that only produce gemmae should have small areas of distribution. Methods: Based on bibliographic information and herbarium data, distribution maps of the Pottiaceae family in Mexico were prepared to detect possible differences in distribution patterns between dioicous and monoicous species. Environmental data were added to refine the grouping of dioicous and monoicous species. Key results: Dioicous and monoicous Pottiaceae differ in number of species. However, two distinct ranges were observed among taxa represented by similar number of records. The dioicous taxa Plaubelia sprengelii var. sprengelii and Weissia jamaicensis are mainly distributed in eastern and southeastern Mexico, while the monoicous species Syntrichia obtusissima and Timmiella anomala are mainly distributed in central and northwestern regions in Mexico. Conclusions: The Pottiaceae species are widely distributed in Mexico regardless of their sexual condition. Gemmae-producing species do not show a restricted or limited distribution. However, species without no sporophytes or gemmae do show narrower ranges.